Education and certification on heart failure of the Heart Failure Association of the European Society of Cardiology - Mullens, Wilfried; Coats, Andrew J.S.; Seferović, Petar M.; Metra, Marco I.; Mebazaa, Alexandre; Ruschitzka, Frank T.; Filippatos, Gerasimos S.; Volterrani, Maurizio; Ponikowski, Piotr P.; Jankowska, Ewa Anita; Chioncel, Ovidiu; McDonagh, Theresa A.; et al. (My University, 2022)
Heart failure (HF) is a devastating chronic and disabling disease with a wide variety of pharmaceutical and device treatment options which are becoming increasingly complex to implement. According to the Heart Failure Association (HFA) Atlas, a subspeciality resource aimed at sourcing contemporary data concerning the epidemiology and healthcare resources for HF, HF is prevalent in17.20 patients per1000 persons, accounting for 2671HFhospitalizations per million inhabitants annually in Europe.1HFpatients also suffer from a high prevalence of non-cardiac comorbidities, which adds complexity to their HF treatment and can negatively impact prognosis.2As a result, HF-related healthcare expenditure continues to rise, and healthcare organizations are becoming faced with the impossible challenge to provide the necessary financial and logistical support to this growing number of patients. In order to address these challenges, the HFA recently outlined the development of quality of care centres (QCC), in order to encourage multidisciplinary management of HF that will improve quality of care and survival.3However, there remains a significant unmet need to train sufficient multidisciplinary teams lead by HF specialists to take care of this expanding group of HF patients. In order to ensure that the next generation of medically-qualified HF specialists will receive high-quality training, this consensus statement of the HFA outlines the requirements for a European training and certification programme for such specialists. The primary goal of this comprehensive educational programme is to increase the quality of patient-centred care related to HF.
Keywords: Heart failure; Quality of care centres; Comprehensive educational programme; Quality of patient-centred